2019
DOI: 10.3389/fneur.2019.00346
|View full text |Cite
|
Sign up to set email alerts
|

Postreperfusion Blood Pressure Variability After Endovascular Thrombectomy Affects Outcomes in Acute Ischemic Stroke Patients With Poor Collateral Circulation

Abstract: Background and Purpose: We evaluated the effect of 24 h blood pressure variability (BPV) on clinical outcomes in acute ischemic stroke patients with successful recanalization after endovascular recanalization therapy (ERT). Methods: Patients with anterior circulation occlusion were evaluated if they underwent ERT based on multiphase computed tomography angiography and achieved successful recanalization (≥thrombolysis in cerebral ischemia 2b). Collateral degrees were dichotomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…Chang et al. (2019) reported that BPV during 48 hr after EVT remained significant to predict functional outcomes at 3 months in AIS patients with poor collateral circulation, whereas no significant association was found between BPV parameters and clinical outcomes in patients with good collateral circulation. Cho and Kim (2019) showed no significant association between SBPV during the first 24 hr after EVT and functional outcomes at 3 months in AIS patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chang et al. (2019) reported that BPV during 48 hr after EVT remained significant to predict functional outcomes at 3 months in AIS patients with poor collateral circulation, whereas no significant association was found between BPV parameters and clinical outcomes in patients with good collateral circulation. Cho and Kim (2019) showed no significant association between SBPV during the first 24 hr after EVT and functional outcomes at 3 months in AIS patients.…”
Section: Resultsmentioning
confidence: 99%
“…Both of the studies showed a significant moderate effect of reperfusion status on the associations between SBPV and functional outcomes. Moreover, Chang et al reported significant associations between BPV and worse functional outcomes at 3 months in AIS patients with poor collateral circulation after EVT, whereas no significant associations were showed between BPV and clinical outcomes in AIS patients with good collateral circulation (Chang et al., 2019). In summary, the damage severity in cerebral autoregulation might moderate the pathophysiological influence of BPV on brain tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported association of BP variability after MT with poor outcome 14,15 but this association was only verified in patients without successful recanalisation or with successful recanalisation but poor collaterals. If recanalisation is not achieved, the ischaemic area is more susceptible to BP changes due to the impaired cerebral autoregulation.…”
Section: Discussionmentioning
confidence: 96%
“… 39 For patients with successful reperfusion after MT, higher BP variability was observed to have a harmful influence on outcomes in those with poor collaterals. 40 …”
Section: Pathophysiologymentioning
confidence: 99%